1972
DOI: 10.1002/chin.197210354
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ZUR UMSETZUNG DES DIAETHYLCHLORPHOSPHINS MIT KETONEN

Abstract: Diäthylchlorphosphin (I) wird im Rohr mit einer Reihe von Ketonen (II) 15 Stdn. auf 95°C erhitzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Simple enones 57 or acryloyl chlorides 60 were shown to produce, respectively methyl substituted or chlorinated oxaphospholenes 59 or 61 when treated with dialkyl halophosphites (Scheme ). In almost the same way, thiocarbonyl compounds gave rise to oxaphospholenes in a reaction with trimethylsilyl dimethyl phosphite…”
Section: Synthetic Routes Towards Oxaphospholenes and Benzoxaphospholmentioning
confidence: 93%
“…Simple enones 57 or acryloyl chlorides 60 were shown to produce, respectively methyl substituted or chlorinated oxaphospholenes 59 or 61 when treated with dialkyl halophosphites (Scheme ). In almost the same way, thiocarbonyl compounds gave rise to oxaphospholenes in a reaction with trimethylsilyl dimethyl phosphite…”
Section: Synthetic Routes Towards Oxaphospholenes and Benzoxaphospholmentioning
confidence: 93%
“…This approach is based on the reaction of accessible phosphorus-containing heterocycles having two P-C bonds, in particular 2-alkyl(aryl)-3,3,5-trimethyl-2,3-dihydro-1,2λ 5 -oxaphosphole 2-oxides like I [8][9][10][11], with Grignard compounds. Hydrolysis of the reaction mixture gives targeted (1-methyl-4-oxopent-2-yl)phosphine oxides II in more than 95% yield.…”
Section: Short Communicationsmentioning
confidence: 99%
“…9 The Michaelis chloride 2 is another easily accessible heterocycle containing one endocyclic phosphorus-carbon bond. 10 Earlier we found that the interaction of the compounds 1 with Grignard reagents leads to the formation of phosphine oxides 4a-e. 12,13 The reaction gives rise to the substitution of both exocyclic P-Cl and endocyclic P-O bonds and allows us to obtain the phosphine oxides with the hydroxy-group in δ-position to the phosphorus atom (Scheme 1). Z-Configuration of double bond of the alkenyl fragment is predetermined by the initial phosphorinine structure.…”
mentioning
confidence: 99%